1994
DOI: 10.1038/hdy.1994.7
|View full text |Cite
|
Sign up to set email alerts
|

Increased recombination frequencies resulting from directional selection for geotaxis in Drosophila

Abstract: Several classes of models have been suggested to explain how natural selection can favour non-zero recombination. Directional and fluctuating selection, abiotic and biotic, and selection against harmful mutations seem to be the most plausible factors, but little has been done to test the problem experimentally. Here we show that long-term selection for positive or negative geotaxis in Drosophila melanogaster results in a dramatic increase in recombination rates in different genomic regions. The total increment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
56
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(61 citation statements)
references
References 26 publications
5
56
0
Order By: Relevance
“…Domestication is typically associated with strong directional selection exerted by breeders, which is known to increase recombination rates (e.g., in Korol and Iliadi, 1994). Increased values of recombination, as measured by chiasmata frequencies, have, in fact, been observed in domesticated mammals (Burt and Bell, 1987) and plants ( Ross-Ibarra, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Domestication is typically associated with strong directional selection exerted by breeders, which is known to increase recombination rates (e.g., in Korol and Iliadi, 1994). Increased values of recombination, as measured by chiasmata frequencies, have, in fact, been observed in domesticated mammals (Burt and Bell, 1987) and plants ( Ross-Ibarra, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…This genetic analysis is consistent with the results obtained in a study that looked at the effects of selection on recombination rates. Korol and Iliadi (1994) selected both positively and negatively for geotaxis in D. melanogaster and observed substantial increases in recombination. Across all regions studied, the map length rose from 217.0 cM in the control line to 295.9 and 283.4 cM in the lines selected for negative and positive geotaxis over a period of 50 generations, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…This has been verified in a number of empirical studies (eg Harinarayana and Murty, 1971;Flexon and Rodell, 1982;Zhuchenko et al, 1985;Burt and Bell, 1987;Wolf et al, 1987;Korol and Iliadi, 1994). The reverse predictionthat is that manipulating the level of recombination should result in changes in the response to selectionhas received some attention to date, with contradictory results (Carson, 1958;McPhee and Robertson, 1970;Markow, 1975;Malmberg, 1977;Thompson, 1977;Zeyl and Bell, 1997;Rice and Chippendale, 2001).…”
Section: Introductionmentioning
confidence: 95%
“…Lond. B (2003) theoretical analysis have shown that directional selection, in combination with nite population size and/or spatial heterogeneity, may promote a selective advantage of increased recombination under much less restrictive assumptions than usually thought (Flexon & Rodell 1982;Gorodetski et al 1990;Korol & Iliadi 1994;Otto & Barton 1997;Korol 1999;Lenormand & Otto 2000). Assuming that sex helps organisms to adapt to adverse conditions, one can further propose that in natural populations of fungi the abundance of sexual forms will be positively correlated with the severity of stress.…”
Section: The Hypothesismentioning
confidence: 99%